Rapid Multiplexed Reduced Representation Bisulfite Sequencing Library Prep (rRRBS) - Legault, Lisa-Marie (Bio Protoc, 2019)
DNA methylation is a common mechanism of epigenetic regulation involved in transcriptional modulation and genome stability. With the evolution of next-generation sequencing technologies, establishing quantitative genome-wide DNA methylation profiles is becoming routine in many laboratories. However, many of these approaches take several days to accomplish and use subjective PCR methods to amplify sequencing libraries, which can induce amplification bias. Here we propose a rapid Reduced Representation Bisulfite Sequencing (rRRBS) protocol to minimize PCR amplification bias and reduce total time of multiplexed library construction. In this modified approach, the precise quantification of the final library amplification step is accomplished and monitored by qPCR, instead of using standard PCR and gel electrophoresis, to determine the appropriate number of cycles to perform. The main advantages of this rRRBS method are: i) Reduced amount of amplification enzyme used for library prep, ii) Reduced number of PCR cycles resulting in less PCR amplification bias, and iii) Preparation of quality multiplexed rRRBS libraries in only ~2 days.